Digital transformation trends in modern Russia - I. V. Borodushko (Путеводитель предпринимателя, 2021)
The article emphasizes the presence and significance of four main areas of digitalization. The interdisciplinary nature of the scientific foundations of digitalization is revealed. The role of the main factors and conditions of digitalization is considered. An assessment of the current level and prospects of digitalization in Russia is presented.